Gifted and telented in the early years: practical activities for children aged 3 to 5 - Sutherland, Magaret (London, 2005)
For the purposes of this book, 'inclusive educa-tion' is taken to mean children learning together: learning from each other, from adults around them and from their communities and families. The focus of this book will be to explore how we can meet the needs of the so-called 'tall poppies' mentioned above within an inclusive education framework.
Keywords: Gifted Children; Gifted Children- Activites and Resources; Talented Children- Assesment